Journalism across cultures : an introduction - Obijiofor, Levi.; Hanusch, Folker, 1975- (Houndmills, Basingstoke, Hampshire, UK ; New York : Palgrave Macmillan, 2011)
"In today's global digital world, journalists are required to be cognizant of ethical and cultural issues beyond usual national boundaries. Drawing on global examples, this text examines international journalism through the authors' wide variety of cultural, educational, teaching and learning backgrounds, including their professional and practical experiences. While existing books tend to be more focused on specific regions or specific aspects of journalism, this book addresses in a comprehensive way journalism across cultures from a truly global (and holistic) perspective. It analyzes media systems in Africa, Latin America, the Arab world and the Middle East, China, as well as North America and Western Europe. This text is truly interdisciplinary in theoretical and practical approaches because it draws on other fields such as media and cultural studies, anthropology, sociology, linguistics, as well as politics and international relations. It will provide an introduction to cross-cultural journalism and equip students with the skills and understanding they need today"--
Machine generated contents note: -- Introduction -- Shifting Theoretical Paradigms: Reconceptualising Theories of the Press and Media Models -- Dimensions of Practice: Journalism Practices across Cultures -- Skilling the Professionals: Journalism and Media Education around the World -- Challenging Old Myths: Foreign News Reporting in the Digital Age -- Promoting a Culture of Peace? Journalistic Approaches to Conflict Resolution -- Who Are We? Identity and Stereotyping in Journalism and Communication -- Challenging Patriarchy in Journalism: Gender in Journalism and Communication -- Packaging Media Products: The Commercialisation of Journalism and Communication -- Changing the Professional Landscape: The Impact of New Technologies on Journalistic Practices -- Conclusions.
Includes bibligraphical references (p. 199-226) and index.
Keywords: Foreign news; Journalism -- History -- 21st century; Journalism -- Moral and ethical aspects; Communication, International; Journalism -- Technological innovations; LANGUAGE ARTS & DISCIPLINES / Journalism; LANGUAGE ARTS & DISCIPLINES / Communication Studies; SOCIAL SCIENCE / Media Studies